2023
DOI: 10.1590/1519-6984.271688
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking, ADMET and molecular dynamics simulation revealed metralindole as a multitargeted inhibitor for division kinases

Abstract: Lung cancer is the most common type of cancer in the world, and alone, in 2020, almost 2.21 million new cases were diagnosed, with 1.80 million deaths, and are increasing daily. Non-small cell lung (NSCLC) is the primary type of lung cancer, predominantly forms around 80% of cases compared to small cell carcinoma, and about 75% of patients are already in an advanced state when diagnosed. Despite notable advances in early diagnosis and treatment, the five-year survival rate for NSCLC is not encouraging. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…On the other hand, the results of ADMET studies of Metralindole 49 showed excellent bioavailability, outstanding solubility, and high safety. These facts encouraged the use of Metralindole as an effective candidate in the treatment of lung cancer …”
Section: Ck2 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the results of ADMET studies of Metralindole 49 showed excellent bioavailability, outstanding solubility, and high safety. These facts encouraged the use of Metralindole as an effective candidate in the treatment of lung cancer …”
Section: Ck2 Inhibitorsmentioning
confidence: 99%
“…These facts encouraged the use of Metralindole as an effective candidate in the treatment of lung cancer. 96 …”
Section: Ck2 Inhibitorsmentioning
confidence: 99%